Iconology of charity - Gerat, Ivan (Peeters, 2020)
The images analyzed in this book give each viewer the possibility to interact with Saint Elizabeth?s unique spiritual way, which was nurtured by various sources, including moments of spontaneous inspiration. The religious leaders who went on to imagine and commission a visual image understood the enormous potential associated with the religious zeal of the extraordinary noble lady as a shining example offering new paths towards Christian charity. The images represent an important testimony of what happened, or rather how the artist or the patron imagined events from the saintþs life. Elizabeth?s extraordinary individual charity has been a source of inspiration to many of her admirers, but the artists and their patrons must have experienced and considered the needs and desires which characterized their period and the communities they were serving. There has been a significant interval between the over-temporal needs or values and contingent historical situations with changing constellations of interests, medial landscapes and rules of political game. The medieval cult of saint Elizabeth awakened the interest of the most influential political figures of the time. Their individual dialogues with the saint connected resonant spiritual messages, which were valid for the duration of any individual?s lifespan, with transient concerns about political struggles, military fights, or materialistic considerations. As a result, the images are multilayered products reflecting human needs and longings on several levels. This book offers a minuscule testimony from this endless flux of feelings, observations and meditations in an effort to broaden slightly the limited range of human experience.
Keywords: Elisabeth; Mitteleuropa; Heiligenverehrung; Legende; Ikonographie; Kunst; Geschichte 1230-1500